De los cuerpos sometidos al silencio: Violencia cultural del género sobre cuerpos masculinos - Muñoz Mejía, Juan David (2023)
The article addresses gender violence, specifically from male bodies. With this, we try to understand how the patriarchal system exerts cultural violence on men through a moral pressure based on not breaking the social norms of gender. Likewise, it is analyzed how punishment, translated into direct violence, is exhibited as a method that legitimizes the violence exerted by male bodies, which approves the gender stereotypes that classify men as an aggressive subject by nature and shows physical violence. as an appropriate means to resolve conflicts. Thus, men are prohibited from showing their emotions, among other consequences, so as not to be excluded from the system. The importance of studying that cultural violence resides in the fact that it is an unnoticed subject and, therefore, silences the bodies that suffer it.